2017
DOI: 10.1111/wrr.12597
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of platelet‐rich plasma therapy in wound healing of pilonidal sinus surgery: A comprehensive systematic review and meta‐analysis

Abstract: Pilonidal disease (PD) is a chronic situation which may cause pain, discomfort, inflammation, discharges, and inability to do daily routines. Among two main methods of surgery, open healing is preferred by surgeons since it associates with lower risk of recurrence; however, it could complicate the wound condition by delaying the healing process. For this meta-analysis, a search in Medline, Embase, and Scopus was performed in June 2017 with no restrictions placed on the publication date or languages. Then, time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…In the first stage of screening titles and abstracts, 79 references were selected. Full texts were scrutinised against the inclusion and exclusion criteria, with a final inclusion of 29 SRs (Figure ) . Reasons for exclusion of studies at the second stage are presented by topic and clinical indication in Files …”
Section: Resultsmentioning
confidence: 99%
“…In the first stage of screening titles and abstracts, 79 references were selected. Full texts were scrutinised against the inclusion and exclusion criteria, with a final inclusion of 29 SRs (Figure ) . Reasons for exclusion of studies at the second stage are presented by topic and clinical indication in Files …”
Section: Resultsmentioning
confidence: 99%
“…Its use as an adjunct in the treatment of pilonidal sinus disease has been evaluated in a meta-analysis in 2017, which included 4 RCTs in surgery with secondary intention healing comparing PRP with the control group (classic dressings). 43 The healing time was found to be significantly shorter in the intervention group (Pooled effect size 0.642, 95% CI 0.485-0.798; P < 0.001), with a mean time to healing of 27.1 days in the PRP group compared with 43.0 days in the control group. The pooled effect size for time to return to work was 0.703 (95% CI 0.539-0.867), with a difference of 9.83 days shorter in the PRP group.…”
Section: Platelet-rich Plasmamentioning
confidence: 89%
“…Platelet‐rich plasma (PRP) is a product described to attempt to accelerate wound healing because of the release of several angiogenic factors upon degradation (vascular endothelial growth factor, insulin‐like growth factor, platelet‐derived angiogenesis factor, and platelet‐derived growth factor). Its use as an adjunct in the treatment of pilonidal sinus disease has been evaluated in a meta‐analysis in 2017, which included 4 RCTs in surgery with secondary intention healing comparing PRP with the control group (classic dressings) . The healing time was found to be significantly shorter in the intervention group (Pooled effect size 0.642, 95% CI 0.485‐0.798; P < 0.001), with a mean time to healing of 27.1 days in the PRP group compared with 43.0 days in the control group.…”
Section: Adjuncts To Surgerymentioning
confidence: 99%
“…“Platelet concentrates” (PCs) is a generic term for different products enriched in platelets . Over the past decade, PCs have been used widely in the regeneration and repair of tissue for wound healing, bone fractures, osteoarthritis, skin rejuvenation, and hair growth . However, their application is confusing and the classification of terminologies for PCs is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, autologous PRP derivatives have been used widely in dermatology, orthopedics, sports medicine, oral/maxillofacial surgery, cardiac surgery, gynecology, ophthalmology, cosmetic surgery, plastic, and reconstructive surgery . However, several studies have reported that PRP has no proven effect .…”
mentioning
confidence: 99%